A rare and unusual presentation of urological infection on a patient on steroids. (13th December 2012) - Kwong, Tsong; Coker, Charles; Simpson, Emma
Abstract : We report the rare case of adult lobar nephronia in a 49-year-old female, on long-term steroids with no prior urological or transplant history. More frequently reported in paediatric literature, adult lobar nephronia (focal pyelonephritis) is an unusual radiological finding sometimes preceding the development of renal abscess. We advocate that treatment should be a prolonged course of antibiotics and close follow-up.